Clinical and urodynamic effects of tolterodine in women with an overactive bladder - Chiu-Lin Wang; Chin-Hu Wu; Cheng-Min Liu; Ching-Ju Shen; Kun-Ling Lin; Cheng-Yu Long (Taiwanese Journal of Obstetrics & Gynecology, 2013)
Objective: The aim of this study was to compare the changes in urinary symptoms and urodynamic parameters after administration of tolterodine in women with an overactive bladder (OAB). Materials and Methods: Thirty-eight women diagnosed with OAB and treated with tolterodine were reviewed. Urinalysis, pelvic examination, 3-day bladder diary, urodynamic study, and a personal interview to identify urinary symptoms prior to and 3 months after treatment were recorded and interpreted. Results: Most of our patients were menopausal (76.3%; mean age 55.7 years) and multiparous (mean parity 3.3) women. Urinary symptoms such as urinary frequency, urgency, urge incontinence, and nocturia were decreased significantly (p < 0.05). All urodynamic parameters did not change significantly except for the maximum cystometric capacity (p < 0.05), showing a significant increase after 3 months of medication. Conclusions: Tolterodine, at a recommended dose, improves the symptoms of OAB syndrome without causing urine retention, as proved by the changes of urodynamic parameters.